“Sovietization” of Traditional Chuvash Culture in the 20-30s of the XX Century - V. V. Medvedev; L. P. Malakhova (Научный диалог)
Questions related to the process of “sovietization” of traditional Chuvash culture are considered. The novelty of the research is seen in the fact that the processes of “sovietization” common to all the peoples of the Soviet Union are examined on the specific material of the Chuvash history collected in the process of ethnographic expeditions. Examples of changing the Chuvash tradition under the influence of cultural impact on the part of the Soviet authorities are brought to consideration. The research shows the ways of penetrating the Soviet type of culture into the people's ritual life. The authors refer to the oikonyms of settlements, anthroponyms, oral folk art and objects of a materialized culture. This material reveals innovations in the everyday life of the ethnic group and the direction of transformation of the people's views. Attention is paid to Soviet symbolism, which has become part of the Chuvash culture. The definitions of the concepts “sovietization”, "materialized culture" are given. Particular attention is paid to the change of consciousness and traditional views, which is most clearly traced in the ritual and festive practice of the Chuvashes. It shown in the research that many objects of “sovietization” retain their relevance, being a part of everyday life or acting as museum exhibits. It is proved that the incorporation of new norms and way of life into the Chuvash tradition led to the formation of a different type of culture - the Soviet one, whose elements are preserved in the modern world.